CTS223 : Creative video production III / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
Experimentation is the keyword in this subject. One of the most important elements in this course is Experimental Thinking as a main focus. Student will be able to understand the concept of Avant-Garde and experimental film. Experimentation here means that, not only in looking film as frames (limited by screen dimension), but more; understanding Video-Art, Conceptual Screen Arts, Computer Graphic/ New Media as tool to develop experimentation process of film/ video making etc. Students can make film/ video in conventional ways, but student also can create ‘video-sculpture’, ‘video assemblage’, ‘experimental animation’ and conceptual-art based from screen. As an art-based faculty, this course will offer students to express their own thought and ideology as content. Practical approach is limitless in producing the result of their final project.